Association of Cardiovascular Health with the Incidence of Venous Thromboembolism: A Prospective Study of 275,149 Participants from the UK Biobank - Liang, Benhui; Zha, Lihuang; Peng, Baohua; Chen, Qin; Juaiti, Mukamengjiang; Zeng, Xiaofang; Feng, Yilu; Yu, Zaixin; Tang, Yiyang (Thrombosis and Haemostasis, 2024)
Background The Life's Essential 8 (LE8) score, recently proposed by the American Heart Association, represents a new paradigm for evaluating cardiovascular health (CVH). We aimed to explore the association between CVH, estimated using LE8, and venous thromboembolism (VTE) incidence.Methods A total of 275,149 participants were recruited from the UK Biobank and divided into high (LE8 score ≥ 80), moderate (LE8 score < 80 but ≥ 50), and low (LE8 score < 50) CVH groups. Restricted cubic spline analysis, the Kaplan–Meier method, and the Cox proportional hazards model were used to explore the association between CVH and VTE. The genetic predisposition to VTE was assessed with a polygenic risk score. Sensitivity analyses were performed to validate the results.Results During a median follow-up of 12.56 years, VTE developed in 506 (4.09%), 6,069 (2.78%), and 720 (1.66%) participants with low, moderate, and high CVH levels, respectively. Compared with the low CVH group, participants in the moderate and high CVH groups had a 23% (hazard ratio [HR]: 0.77; 95% confidence interval [CI]: 0.71–0.85) and 41% (HR: 0.59; 95% CI: 0.52–0.66) lower risk of VTE, respectively, after adjusting for demographic characteristics, medical history, socioeconomic status, and genetic predisposition. This association remained robust in multiple sensitivity analyses. Higher CVH levels led to a more pronounced reduction in the risk of VTE in females and could appreciably offset the genetic risk of VTE.Conclusion Higher CVH levels were significantly associated with a lower incidence of VTE, encouraging efforts to increase LE8 scores in individuals.
Keywords: cardiovascular health; Life's Essential 8; venous thromboembolism; genetic predisposition